Evaluation of salivary oxidative parameters in overweight and obese young adults - Chielle, Eduardo Ottobelli; Casarin, Jeferson Noslen (Archives of Endocrinology and Metabolism, 2017)
Obesity is characterized by a deposition of abnormal or excessive fat in adipose tissue, and is linked with a risk of damage to several metabolic and pathological processes associated with oxidative stress. To date, salivary oxidative biomarkers have been minimally explored in obese individuals. Thus, the aim of this study was to assess the concentrations of salivary oxidative biomarkers (ferric-reducing antioxidant power, uric acid, sulfhydryl groups) and lipid peroxidation in obese and overweight young subjects. Levels of lipid peroxidation, ferric-reducing antioxidant power, uric acid, and SH groups were determined in the saliva and serum of 149 young adults, including 54 normal weight, 27 overweight, and 68 obese individuals. Anthropometric measurements were also evaluated. Salivary levels of ferric-reducing antioxidant power, sulfhydryl groups, and lipid peroxidation, as well as serum levels of ferric-reducing antioxidant power, uric acid, and lipid peroxidation were higher in obese patients when compared with individuals with normal weight. There were correlations between salivary and serum ferric-reducing antioxidant power and salivary and serum uric acid in the obese and normal-weight groups. Our results indicate that the increase in salivary levels of ferric-reducing antioxidant power, sulfhydryl groups, and lipid peroxidation, and serum levels of ferric-reducing antioxidant power, uric acid, and lipid peroxidation could be related to the regulation of various processes in the adipose tissue. These findings may hold promise in identifying new oxidative markers to assist in diagnosing and monitoring overweight and obese patients.